The elusive brain perivascular fibroblast: a potential role in vascular stability and homeostasis - Sosa, Maria J.; Shih, Andy Y.; Bonney, Stephanie K. (Frontiers in Cardiovascular Medicine, 2023)
In the brain, perivascular fibroblasts (PVFs) reside within the perivascular spaces (PVSs) of arterioles and large venules, however their physiological and pathophysiological roles remain largely unknown. PVFs express numerous extracellular matrix proteins that are found in the basement membrane and PVS surrounding large diameter vessels. PVFs are sandwiched between the mural cell layer and astrocytic endfeet, where they are poised to interact with mural cells, perivascular macrophages, and astrocytes. We draw connections between the more well-studied PVF pro-fibrotic response in ischemic injury and the less understood thickening of the vascular wall and enlargement of the PVS described in dementia and neurodegenerative diseases. We postulate that PVFs may be responsible for stability and homeostasis of the brain vasculature, and may also contribute to changes within the PVS during disease.